Implementation of User Anthropometry Bale “Sakenem” Buildings based on Height Bataran and Height Bale-bale in Singapadu Tengah Village, Gianyar - I Wayan Parwata; Anak Agung Gede Oka Wisnumurti; Ni Wayan Meidayanti Mustika (Universitas Lampung, 2016)
Abstract—Bale Sakenem Building is one of the buildings that were in the order of Traditional Bali House. This study identified Bale Sakenem building located in the Central Singapadu Village and that is observational research by using cross sectional design. This research was done by means of retrospective observational that is considered the factor that can affect Bale Sakenem Building Anthropometry. From the data analyze of research identification, 30% height bataran not in accordance with the average size of an ideal height bataran and 20% height bale-bale also not in accordance with the average of the ideal height bale-bale in Bale Sakenem building in the Central Singapadu Gianyar have not yet undertaken anthropometry users and more dominant to follow measurements that based on the size of Undagi, as a consequence there was uncomfortableness. Height bataran and height bale-bale is based on the tolerance of anthropometry using the 95 percentile and 5 percentile for tolerance limitKeywords—Anthropometry, Balinese Architecture, Culture, Percentile, User Comfort.